Effect of artifacts upon the pressure reactivity index - Rozanek, Martin; Skola, Josef; Horakova, Lenka; Trukhan, Valeriia (Scientific reports, 2022)
The pressure reactivity index (PRx) is a parameter for the assessment of cerebrovascular autoregulation, but its calculation is affected by artifacts in the source biosignals-intracranial pressure (ICP) and arterial blood pressure. We sought to describe the most common short-duration artifacts and their effect on the PRx. A retrospective analysis of 935 h of multimodal monitoring data was conducted, and five types of artifacts, characterized by their shape, duration, and amplitude, were identified: rectangular, fast impulse, isoline drift, saw tooth, and constant ICP value. Subsequently, all types of artifacts were mathematically modeled and inserted into undisturbed segments of biosignals. Fast impulse, the most common artifact, did not alter the PRx index significantly when inserted into one or both signals. Artifacts present in one signal exceeded the threshold PRx in less than 5% of samples, except for isoline drift. Compared to that, the shortest rectangular artifact inserted into both signals changed PRx to a value above the set threshold in 55.4% of cases. Our analysis shows that the effect of individual artifacts on the PRx index is variable, depending on their occurrence in one or both signals, duration, and shape. This different effect suggests that potentially not all artifacts need to be removed.
Keywords: mozkový krevní oběh; intrakraniální tlak; Humans; Intracranial Pressure; retrospektivní studie; traumatické poranění mozku; Brain Injuries, Traumatic; Arterial Pressure; Cerebrovascular Circulation; Retrospective Studies; arteriální tlak; Artifacts; lidé; artefakty